The power of community engagement for educational change - Evans, Michael P.; Hiatt-Michael, Diana B. (Family, school, community, partnership issues., 2016)
Effective schools engage a wide range of families and community members to support their award-winning programs. This monograph highlights exemplary examples of communities, including foundations, community organizers, non-profit organizations, community agencies, as well as school districts, that lead successful group, school, district and state level initiatives to improve educational outcomes.Practitioners and scholars join hands to share promising practices and research-based examples of community initiatives that have had positive impacts on families, schools, and communities. This monograph is vital to educational leadership preparation programs; education policymakers at the local, state, and national levels; school and district level administrators; and a broad range of community leaders.